KEANEKARAGAMAN JENIS ANGGOTA LAURACEAE DAN PEMANFAATANNYA DI CAGAR ALAM DUNGUS IWUL KABUPATEN BOGOR JAWA BARAT - Seviana Mulia; M Murningsih; J Jumari; Lade Alhamd (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2017)
Lauraceae is a group of flower plant that have a significant economic value. In the Natural Preserve of Dungus Iwul has been identified the existence of the Lauraceae family. The purpose of this research is to determine the diversity of Lauraceae species, understand Lauraceae density and frequency in Natural Preserve of Dungus Iwul, and understanding it’s utilization. The observation was done on 1 ha plot sample, which include identification, inventarization, and the collection of the Lauraceae species, the research was done on May until June 2016. There are 48 individual members of the Lauraceae species which is consist of nine species and 4 genera, e.g. Cryptocarya, Litsea, Actinodaphne, Cinnamomum. The highest density value were Litsea racemosa C.T White with 29,79% as relative density and the lowest density were Cinnamomum javanicum Blume and Litsea resinosa Blume with 2,13% as relative density. The species with the highest frequency were Litsea racemosa C.T White with 24,32% as relative frequency value and the species with the lowest frequency were Cinnamomum javanicum Blume dan Litsea resinosa Blume with 2,70% as relative frequency value. The Lauraceae family have benefits such as animal feed, building materials, cover crops, ornamental plants, industrial raw materials, essential oil, and act as a medicine.Keywords : Lauraceae, Natural Preserve of DungusIwul, species diversity, density and frequency plants utilization.